Behavioral characterization of mice lacking Trek channels - Mirkovic, Kelsey; Palmersheim, Jaime; Lesage, Florian; Wickman, Kevin (Frontiers in Behavioral Neuroscience, 2012)
Two-pore domain K+ (K2P) channels are thought to underlie background K+ conductance in many cell types. The Trek subfamily of K2P channels consists of three members, Trek1/Kcnk2, Trek2/Kcnk10, and Traak/Kcnk4, all three of which are expressed in the rodent CNS. Constitutive ablation of the Trek1 gene in mice correlates with enhanced sensitivity to ischemia and epilepsy, decreased sensitivity to the effects of inhaled anesthetics, increased sensitivity to thermal and mechanical pain, and resistance to depression. While the distribution of Trek2 mRNA in the CNS is broad, little is known about the relevance of this Trek family member to neurobiology and behavior. Here, we probed the effect of constitutive Trek2 ablation, as well as the simultaneous constitutive ablation of all three Trek family genes, in paradigms that assess motor activity, coordination, anxiety-related behavior, learning and memory, and drug-induced reward-related behavior. No differences were observed between Trek2–/– and Trek1/2/Traak–/– mice in coordination or total distance traveled in an open-field. A gender-dependent impact of Trek ablation on open-field anxiety-related behavior was observed, as female but not male Trek2–/– and Trek1/2/Traak–/– mice spent more time in, and made a greater number of entries into, the center of the open-field than wild-type counterparts. Further evaluation of anxiety-related behavior in the elevated plus maze and light/dark box, however, did not reveal a significant influence of genotype on performance for either gender. Furthermore, Trek–/– mice behaved normally in tests of learning and memory, including contextual fear conditioning and novel object recognition, and with respect to opioid-induced motor stimulation and conditioned place preference. Collectively, these data argue that despite their broad distribution in the CNS, Trek channels exert a minimal influence on a wide-range of behaviors.